Fintech Innovation Research: Four Clusters Mapping - Uula, Mimma Maripatul; Devi, Abrista (Journal of Islamic Economics Literatures, 2024)
This study aims to see the development of research on the topic of "Fintech Innovation" and research plans that can be carried out based on journals published on the theme. This research uses an qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Fintech Innovation" which comes from the Dimension database with a total of 3094 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Fintech Innovation" research development in the world. The results of the study found that in bibliometric author mapping the authors who published the most research with the theme "Fintech Innovation" were Rabbani, Mustafa Raza; Wonglimpiyarat, Jarunee; Peng, Kuan-Jung; and Mohammed, Qmichchou. Furthermore, based on bibliometric keyword mapping, there are 4 clusters with the most used words including sharia bank, financial inclusion, application, factor, adoption, country, effect, challenge, financial institution, regulation, and performance. Then, the research path topics related to Fintech Innovation are Collaboration Between Fintech Startups and Traditional Banks, Mechanisms of Green Innovation in the Fintech Sector, Value and Complexity in Fintech Application Use, and Islamic Fintech's Role in Pandemic-Era Financial Solutions.